Acupuncture for metabolic syndrome: systematic review and meta-analysis. Issue 4 (August 2021) - Li, Xue; Jia, Hong-Xiao; Yin, Dong-Qing; Zhang, Zhang-Jin
Background: Metabolic syndrome (MetS) is a cluster of conditions associated with an increased risk of cardiovascular disease and diabetes mellitus. Acupuncture may have benefits in the treatment of MetS. This systematic review with meta-analysis aimed to determine the effectiveness and safety of acupuncture therapy in the treatment of MetS. Methods: Large-sample randomized controlled trials (RCTs) of acupuncture treatment for MetS were extracted from multiple Chinese and English databases and analyzed using meta-analysis to evaluate the efficacy/effectiveness of acupuncture with respect to various MetS indices in comparison with control treatments including conventional medications (CMs) and lifestyle intervention (LI), together and separately. Results: A total of 13 RCTs were identified with 423 subjects undergoing acupuncture regimens and 411 receiving control interventions. Active acupuncture yielded better outcomes than sham acupuncture with respect to improving multiple MetS indices. Acupuncture monotherapy had similar effectiveness in controlling triglyceride levels and high-density lipoprotein levels compared to CMs. The overall effects of adjunctive acupuncture were markedly greater than those of controls (CMs + LI, CMs, and LI) with respect to waist circumference with a mean difference of −5.11 cm (Z = 4.57, p < 0.001) and body mass index with a mean difference of −2.54 (Z = 5.38, p <0.001), and improvements were observed in most hyperlipidemia indices and fasting blood glucose. An evidence-based acupuncture regimen was identified as a future treatment strategy for MetS. Conclusion: Acupuncture is beneficial in the treatment of MetS and could serve as an alternative therapy for MetS-associated conditions. Larger-scale RCTs are needed to confirm the efficacy/effectiveness of our recommended evidence-based acupuncture regimen in MetS.